2023
DOI: 10.1001/jamanetworkopen.2023.21947
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Rates of Opioid Agonist Treatment and Opioid-Related Deaths for Youths in Ontario, Canada, 2013-2021

Abstract: ImportanceData suggest that the opioid crisis in North America has recently been reflected in opioid-related mortality among youths. Despite recommendation for its use, youths encounter barriers to accessing OAT, including stigma, burden of witnessed dosing, and lack of availability of youth-oriented services and prescribers comfortable treating this population.ObjectiveTo compare rates of opioid agonist treatment (OAT) and opioid-related mortality between youths aged 15 to 24 years and adults aged 25 to 44 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Many physicians and medical students are not aware that there are effective treatments for SUD and that the patients are not a "lost cause". It is mind-boggling that less than 25% of individuals with OUD are enrolled in evidence-based opiate agonist therapy (OAT) [4].…”
Section: Editorialmentioning
confidence: 99%
“…Many physicians and medical students are not aware that there are effective treatments for SUD and that the patients are not a "lost cause". It is mind-boggling that less than 25% of individuals with OUD are enrolled in evidence-based opiate agonist therapy (OAT) [4].…”
Section: Editorialmentioning
confidence: 99%
“…Orthopaedic surgeons frequently overprescribe opioid medications, even in the adolescent and young adult population, which can be saved by patients and thus can be at high risk for later misuse or diversion 2-7 . A cross-sectional analysis of public health data from Ontario, Canada, found that a youth population <25 years of age experienced a 369.2% increase in opioid-related deaths from 2013 to 2021 8 and male patients of this age were at especially high risk for opioid use disorder and overdose 9 . Despite these risks, recent reports have suggested that surgeons are biased toward providing patients of this demographic group with a higher-quantity postoperative prescription 10 .…”
mentioning
confidence: 99%